Кадрові ресурси освіти в контексті забезпечення сталого розвитку - Гаращук, О.В.; Куценко, В.І. (Економіка природокористування і охорони довкілля, 2015)
Розкривається сутність і значення кадрових ресурсів вищої освіти, їх роль у підвищенні якості освіти, забезпеченні сталого розвитку, формуванні економіки знань. Наведено характеристику останньої. Аналізується мережа закладів вищої освіти України, її кадрові ресурси по регіонах. Розроблено модель сучасного викладача вищого навчального закладу в аспекті його особистісних професійних характеристик. Рекомендуються заходи, реалізація яких сприяла б підвищенню професійно-кваліфікаційного рівня викладацького складу з використанням різних методичних підходів. Обґрунтовано доцільність розробки в кожному навчальному закладі системи підвищення професійно-кваліфікаційного рівня професорсько-викладацького складу за методологією, що базується на широкому спектрі наукових принципів. The essence and importance of human resources in higher education. Underlines their role in improving the quality of education, sustainable development, the formation of knowledge economy. The characteristics specified economic model. We analyze the parameters of the existing network of higher educational institutions of Ukraine, its human resources by comparing the population of different regions, the number of students with the presence among human resources PhDs. A model of the modern university teachers as a professional. Served characteristic features of modern Japanese teacher school. Settle measures, implementation of which would contribute to ensure the increase of professional qualification of the teaching staff, based on the use of different methodological approaches. The necessity of development in each school system of increase of professional qualification of faculty members, using a methodology, which was based on a wide range of scientific principles.